Captopril fast disintegrating tablets for children: formulation and quality control by HPLC - Shohreh Alipour; Asiyeh Mohammadi; Fatemeh Ahmadi (Trends in Pharmaceutical Sciences, 2017)
Captopril is an angiotensin converting enzyme inhibitor, which is used in hypertensive crises and heart failures as an emergency medication especially in pediatrics. Due to difficulty in swallowing of tablets and capsules, pediatric compliance for medication usage is a big challenge in formulation. Considering captopril instability in oral liquid media, it should be formulated as a solid dosage form. Using fast disintegrating tablets (FDTs) is an attractive strategy for solving this problem. According to captopril ultra violet absorption spectrum, high performance liquid chromatography (HPLC) seems to be an accurate, reproducible, and precise method for analysis. Captopril HPLC method was developed and validated for linearity, accuracy, and precision. Because of captopril unacceptable taste especially for children, Eudragit E was used as a taste masking polymer to prepare granules. Crospovidon and Ac-Di-Sol were used as super-disintegrants to reduce tablet disintegration time. Flavoring agents are important ingredients in formulating FDTs for children. Different FDT formulations were prepared by direct compression and granulation-compression method. Quality test of tablets such as thickness, weight, friability, hardness, disintegration time, dissolution profile, and taste masking power were also examined. HPLC validation was confirmed by r2=0.9994, accuracy of 97.4 ± 2.3%, and inter and intra-day precisions of 97.6±1.2 and 97.3± 2.1, respectively. The optimized tablets showed suitable friability (0.85%), hardness (4.1N), and disintegration time (40 sec) with a desirable taste related to presence of Eudragit E. An appropriate and complete dissolution profile within 30 min was also achieved. Results confirmed that captopril taste-masked FDTs would be a pleasant alternative for the available tablets in the market for using in children.